Correlation between Skeletal Age and Metacarpal Bones and Metacarpophalangeal Joints Dimensions - Abdolaziz Haghnegahdar; Hamidreza Pakshir; Ilnaz Ghanbari (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Currently, two major methods have been introduced for bone age assessment using left hand radiography. The first approach is Greulich and Pyle, which is very subjective. The second method is Tanner and Whitehouse, which is very time consuming and its morphological criteria are not quantitative, therefore it is hardly used. Purpose: The purpose of this study is to evaluate the relationship between skeletal age and bone size and joint space measurements among Asian children using hand radiographs and using this correlation as an aid in determining bone age. Materials and Method: In this analytic research, 304 hand radiographs from Asian children with normal development have been included in this study (155 female, 149 male). Two radiologists using Greulich and Pyle method assessed their bone ages. The 2nd-5th metacarpal bones length and width and 2nd-5th metacarpophalangeal joints width and length were manually measured by Adobe Photoshop and compared with subjects' skeletal age. Pearson correlation was used to determine the relationship. Results: Pearson correlation between bone age and metacarpal bones length was 0.902-0.938; metacarpal bones width was 0.452-0.850; metacarpophalangeal joints width was 0.656 - 0.811, and metacarpophalangeal joints length was 0.920 - 0.947. Conclusion: Regarding Pearson correlation, metacarpophalangeal joints length, metacarpal bones length, metacarpophalangeal joints width, and metacarpal bones width showed significant relationship with bone age, respectively. These measurements can be used as accessory criteria for bone age assessment using left hand radiography, to reduce inter-observer reading differences.